A Benzothiadiazole-Based Zn(II) Metal–Organic Framework with Visual Turn-On Sensing for Anthrax Biomarker and Theoretical Calculation - Jing Ru; Yi-Xuan Shi; Qing-Yun Yang; Teng Li; Hai-Ying Wang; Fan Cao; Qiang Guo; Yan-Lan Wang (Molecules, 2024)
2,6-pyridine dicarboxylic acid (DPA) is an exceptional biomarker of notorious anthrax spores. Therefore, the rapid, sensitive, and selective quantitative detection of DPA is extremely significant and urgent. This paper reports a Zn(II) metal–organic framework with the formula of {[Zn6(NDA)6(DPBT)3] 2H2O·3DMF}n (MOF-1), which consists of 2,6-naphthalenedicarboxylic acid (2,6-NDA), 4,7-di(4-pyridyl)-2,1,3-benzothiadiazole (DPBT), and Zn(II) ions. Structural analysis indicated that MOF-1 is a three-dimensional (3D) network which crystallized in the monoclinic system with the C2/c space group, revealing high pH, solvent, and thermal stability. Luminescence sensing studies demonstrated that MOF-1 had the potential to be a highly selective, sensitive, and recyclable fluorescence sensor for the identification of DPA. Furthermore, fluorescent test paper was made to detect DPA promptly with color changes. The enhancement mechanism was established by the hydrogen-bonding interaction and photoinduced electron transfer transition between MOF-1 and DPA molecules.